CONSIDERAŢII MEDICO-LEGALE PRIVIND ANESTEZIA LOCO-REGIONALĂ ÎN MEDICINA DENTARĂ - Oana Elena Ciurcanu; Doriana Agop-Forna (Romanian Dental Association for Education, 2018)
The problem of the interventions performed under loco-regional anesthesia - practiced in a dental office, must be seen in the context of increasing plurifactorial dental care in Romania, in private or public practice. Because of the many advantages it presents, loco-regional anesthesia is considered as a method household during dental care routine. Currently, anesthesia allows adaptation methods and techniques individualized for each patient, so as to benefit from a perfect anesthesia and with minimal risk. Modern medicine attaches great importance to prevention of incidents, accidents and complications in surgical techniques, anesthesia loco-regional not an exception. Anesthesiology is one of the medical specialties related to medical malpractice can sometimes have complications leading to death of the patient; errors are inadmissible in this area.